Malnutrition: risks & concerns in dysphagia management - Yarrow, Linda; Garcia, Jane Mertz (My University, 2011)
Malnutrition, particularly undernutrition, negatively affects health outcomes. Risk of malnutrition, often identified by a Registered Dietitian as part of a patient's dietary assessment, increases greatly in the presence of dysphagia. Patient characteristics that may be linked to malnutrition include advanced age, medical diagnoses, level of diet tolerated, actual calorie and protein intake, need for feeding assistance, weight changes, and quality of life issues. Many older adults may be malnourished at the time of their hospital admission or become so during the course of their medical care. Poor physical condition from malnutrition could negatively impact a patient's rehabilitation potential. This article highlights possible causes and effects of undernutrition and the importance of nutrition strategies to patient care through a case study illustration.
Keywords: Malnutrition; Dysphagia